1990
DOI: 10.1111/j.1469-8749.1990.tb16945.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure Index of Walking for Normal Children and for Children With Cerebral Palsy

Abstract: SUMMARY Energy expenditure indices (EEI) based on oxygen uptake and heart rate were used to compare the economy of walking at various speeds by normal and cerebral‐palsied children. At low walking speeds, EEI values were high, indicating poor economy. At higher speeds the EEI values decreased until a range of maximum economy was reached. For normal children who were capable of walking beyond this range at higher speeds, the EEI increased again. This pattern was noted for both oxygen‐uptake and heart‐rate indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
0
4

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(98 citation statements)
references
References 18 publications
6
88
0
4
Order By: Relevance
“…Overall stride length was found to be greater among younger workers compared to aged workers. Rose et al [7] shows similar result, in which young adults showed a greater increase than did the aged subjects. While the changes in gait characteristics were relatively small for the young subjects, the older population was affected to a greater extent thereby demonstrating a greater sensitivity to load magnitude in a load carriage task.…”
Section: Resultsmentioning
confidence: 65%
“…Overall stride length was found to be greater among younger workers compared to aged workers. Rose et al [7] shows similar result, in which young adults showed a greater increase than did the aged subjects. While the changes in gait characteristics were relatively small for the young subjects, the older population was affected to a greater extent thereby demonstrating a greater sensitivity to load magnitude in a load carriage task.…”
Section: Resultsmentioning
confidence: 65%
“…For example, children with hypotonic and non-ambulatory CP did not require calories more than that to sustain the resting energy expenditure (31); while children with athetoid CP had an increased demand for calories (32,33). Similarly, children with diplegic or hemiplegic CP required more calories to sustain their daily activities than the normal children (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several are the instruments to assess the gait, which aim at understanding the biomechanical changes and also the energy cost to run it 5 . Seeking greater ease of measurement of energy expenditure during the gait of children, Rose et al 6 compared the energy expenditude index (EEI) by oxygen with the rate of energy expenditure by heart rate (HR) and concluded that, although both of them may be used in the evaluation of normal children and children with cerebral palsy, it is preferable to use the index obtained by HR, given its ease of data acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…The EEI, whose final result is expressed as number of heartbeats per meter walked 5 , is usually reported in children with cerebral palsy [6][7][8][9] , however restricted to works in patients with DMD. In these patients, the resting energy expenditure, measured by calorimetry, is the target of most studies [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%